Seminars in consultation-liaison psychiatry - Guthrie, Elspeth; House, Allan; Thomasson, Rachel (Cambridge University Press, 2024)
Consultation-liaison psychiatry has evolved rapidly in the last decade, with significant expansion of services across the UK. Now in its third edition, Seminars in Consultation-Liaison Psychiatry provides a current, comprehensive, practically orientated guide that covers clinical topics, education, service development, audit and research. New and updated chapter topics cover the presentation, diagnosis, and management of common conditions, and chapters on organisational topics provide insights into developing and managing the context within which practice takes place. Each chapter is informed by the latest research while remaining hands-on in its focus, structured around common clinical scenarios that liaison staff encounter in hospital settings. A practical guide, this book is packed with essential reading for clinicians working at the interface between mental and physical healthcare.